Determination of Diagnostic Reference Levels for Chest Examination for Windhoek, Namibia - David, E.L.M; Daniels, E.; Uushona-Mikka, V. (Namibian Journal for Research, Science and Technology, 2018)
The widespread use of X-ray examination has improved lives worldwide and this evolution of imaging has also resulted in a significant increase in the population’s exposure to ionizing radiation. This exposure can be minimised by the setting up Diagnostic Reference Levels (DRLs). DRLs are exposure level that serve as guide for standard regions of interest and are recommended by the International Atomic Energy Agency for member states to apply within the context of the national legislation. Namibia Radiation Protection and Waste Disposal Regulations also mandate the National Radiation Protection Authority to determine guidance levels as a condition of a license. Management of patient dose and determination of DRLs are important part of quality control programs in X-ray diagnostic departments as it forms an efficient and powerful standard for minimising radiation dosage to patients. Since Namibia has not yet established DRLs, the aim of this study was to develop DRLs for posterior anterior (PA) chest examination in Windhoek, Namibia. Quality control tests were done on the X-ray machines using a Xi-Unfors radiation meter. Entrance skin doses (ESDs) were obtained from 120 patients that were referred for chest examination at the six selected facilities in Windhoek. The following parameters were measured: kilovoltage peak (kVp), milliampere seconds (mAs), the focus to bucky distance (FBD) and focus to surface distance (FSD). The ESDs were then calculated. The average ESD was found to be 0.47 mGy, ranging from 0.14 to 1.3 mGy. The study provided baseline information on ESD’s for PA chest radiography. The ESD’s in this study was above the ESD’s recommended by the IAEA which is 0.2mGy. This was attributed to the use of high kVp and mAs and a short FBD at some facilities. The results of this study, with more data expected to be collected by the National Radiation Protection Authority (NRPA) will provide a useful baseline to establish Namibia’s DRLs.